2020
DOI: 10.1111/iji.12490
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetics of the major histocompatibility complex in humans and nonhuman primates

Abstract: The major histocompatibility complex (MHC) is one of the most gene-dense regions of the mammalian genome. Multiple genes within the human MHC (HLA) show extensive polymorphism, and currently, more than 26,000 alleles divided over 39 different genes are known. Nonhuman primate (NHP) species are grouped into great and lesser apes and Old and New World monkeys, and their MHC is studied mostly because of their important role as animal models in preclinical research or in connection with conservation biology purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 142 publications
(209 reference statements)
0
24
0
1
Order By: Relevance
“…In previous studies, five DQA alleles and six DQB alleles were reported from just one Saguinus oedipus individual [ 40 ] and five DQB alleles in an Aotus nancymaae individual were confirmed [ 20 ]. Thus, the presence of a third set of DQ genes has now been demonstrated in three platyrrhine families despite the continued emphasis of two DQ copies that are orthologous with hominids [ 60 , 61 ]. Understanding whether these additional DQ gene copies are functional or pseudogenes will require more genetics research.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, five DQA alleles and six DQB alleles were reported from just one Saguinus oedipus individual [ 40 ] and five DQB alleles in an Aotus nancymaae individual were confirmed [ 20 ]. Thus, the presence of a third set of DQ genes has now been demonstrated in three platyrrhine families despite the continued emphasis of two DQ copies that are orthologous with hominids [ 60 , 61 ]. Understanding whether these additional DQ gene copies are functional or pseudogenes will require more genetics research.…”
Section: Resultsmentioning
confidence: 99%
“…Each animal facility has different environmental stressors/stimuli, where certain containments or facilities are maintained under germ-free conditions. Genetic variations in major histocompatibility complex exist among different NHP species or sub-populations (Viray, Rolfs & Smith, 2001;Heijmans, De Groot & Bontrop, 2020). This would potentially generate species or population-specific immune responses even when exposed to the same antigenic/environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее следует учитывать, что выраженность молекулярной мимикрии между белками вируса и хозяина для обезьян может отличаться от проявления данного феномена у человека. Так, разнообразие генов белков MHC у этих животных шире, чем у людей [50]. Совпадение белковых последовательностей вируса и организма хозяина может существенно влиять на выраженность иммунного ответа и степень риска развития осложнений аутоиммунного характера.…”
Section: макак-резусыunclassified